Ubezpieczenia w Polsce po akcesji do Unii Europejskiej - Przybytniowski, Jarosław W. (Insurances in Poland After Accession to the European Union, 2008)
The aim of the article was an analysis of the Polish insurance market after accession to the European Union by prism of the PZU Group. This analysis is especially interesting in time of liberalization and consolidation with regard to predominant insurers' market position. The PZU Group is one of the largest financial institutions in Poland. It deals with insurance activity, in range of management of life annuity fund, investments fund and economizing programmes. Until the end of 2005 the PZU Group created 24 subjects testifying services in range of insurances: insurance of property, Life and accident insurances and Investing Funds and Life Annuity Open Fund. Polish insurance market marks high coefficient of commitment foreign capital in insurance business. Nevertheless, those insurance companies with national capital make up minority in section I and II, they has been still generating the higher gross written premium. It happens mainly for cause of PZU SA PZU for life SA. The percentage share in market of PZU SA and PZU for life SA is successive diminishing. However, in spite of market déconcentration, PZU SA and PZU for life SA, still occupies the leaders' position in their sections. The analysis of height and dynamics of gross written premium of two largest subjects of Group, permit to suppose that it will be developing in stable way, without any violent swirls.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 386-394